Research on mechanism and control of asymmetric deformation of gob side coal roadway with fully mechanized caving mining. (February 2021) - Xu, Xuhui; He, Fulian; Li, Xiaobin; He, Wenrui
Highlights: The asymmetric failure mechanism of coal pillar roadway was revealed. The limit caving thickness of studied mine was determined. A special surrounding rock support technology was proposed. Abstract: Considering serious asymmetric deformations and failures of the gob side roadway in fully mechanized top coal caving face and taking coal pillar roadway as engineering background, we have discussed the surrounding stress condition and the deformation failure patterns of coal pillar roadway by the theoretical analysis, numerical calculation, field tests. The results show that the deformations and failures of gob side coal roadway with fully mechanized caving mining are characterized by "two-way" asymmetric failure patterns along vertical and horizontal directions. The reason for the asymmetric deformation was uneven stress conditions of surrounding rocks under the effect of strong mining. The asymmetric deformations and failures of coal pillar roadway surrounding rocks were closely related to caving thickness in former panel. The fracture position of main roof varied with top coal thickness, and limit caving thickness was 9.4 m. Based on the asymmetric deformation characteristics and mechanisms of roadway, this paper has proposed a control strategy which mainly adopts asymmetric high prestressed truss anchor cable. Field tests were carried out in the repair section of roadway. The results show that roadway asymmetric deformation was well controlled and long-term stability of roadway was realized, which provides a reference for similar asymmetric deformation roadway.